PENGARUH OBJEKTIVITAS DAN INTEGRITAS AUDITOR INTERNAL TERHADAP KUALITAS AUDIT - Fitriani, Indah (Jurnal Riset Akuntansi dan Keuangan, 2013)
This research is aim to know the influence of objectivity and integrity of internal auditors towards the audit quality partially and simultaneously, whether it significantly affects or not towards the audit quality on Inspektorat Daerah of Kota Bandung, Kota Cimahi, Kabupaten Bandung, and Kabupaten Bandung Barat. The method used for this research is the descriptive method, and the analysis used is the multiple linear regression analysis. The sampling technique for this research is saturated sampling. The result of the research with 5% signification level shows that objectivity and integrity of internal auditors simultaneously influences the audit quality where the value F (91,837) the table F (3,232), and objectivity of auditor partially influences significantly the audti quality where the value T (4,914) the table T (2,021) as well as the integrity of auditor influences significantly the audit quality where the value T (10,721) is bigger than the table T (2,021).